Modeling, simulation, and analysis of birefringent effects in plastic optics - Adhikari, Achyut (2018)
Plastic optics has been widely used in different application. They have been facing birefringent effects during manufacturing or during certain application. Finite element modeling of plastic optics in CAD interface is done along with experimental and theoretical comparison of the specimen with the help of solid mechanics and image processing. Low birefringence plastic optics is chosen for the experiment and varying load is applied to observe the characteristics both in experiment and simulation. Low birefringence polariscope was used to measure the birefringence in the plastic specimen. Birefringence is caused due to many effects like stress induced birefringence temperature induced due to thermal gradient and pressure during manufacturing. Here stress is induced on low birefringence specimen by two point compression loading and is compared on the base of solid mechanics, finite element modeling and image processing. The results were found to be similar and convincing.